Alcohol outlet density and alcohol consumption in Los Angeles county and southern Louisiana - Matthias Schonlau (Geospatial Health, 2008)
The objective of this study was to assess the relationship between alcohol availability, as measured by the density of off-premise alcohol outlets, and alcohol consumption in Los Angeles county and southern Louisiana, USA. Consumption information was collected through a telephone survey of 2,881 households in Los Angeles county and pre-Katrina southern Louisiana, nested within 220 census tracts. Respondents’ addresses were geo-coded and both neighbourhood (census tracts and buffers of varying sizes) and individual (network distance to the closest alcohol outlet) estimates of off-sale alcohol outlet density were computed. Alcohol outlet density was not associated with the percentage of people who were drinkers in either site. Alcohol outlet density was associated with the quantity of consumption among drinkers in Louisiana but not in Los Angeles. Outlet density within a one-mile buffer of the respondent’s home was more strongly associated with alcohol consumption than outlet density in the respondent’s census tract. The conclusion is that the relationship between neighbourhood alcohol outlet density and alcohol consumption is complex and may vary due to differences in neighbourhood design and travel patterns.